VASCULAR COMORBIDITY: GENERAL APPROACHES TO PREVENTION AND TREATMENT - R. G. Oganov (Рациональная фармакотерапия в кардиологии)
The problem of vascular comorbidity in patients with cardiovascular diseases, its effect on the cardiovascular risk, general causes and approaches to the prevention and treatment of vascular comorbidity are considered.